Atomic evidence that modification of H-bonds established with amino acids critical for host-cell binding induces sterile immunity against malaria (2010)
Based on the 3D X-ray crystallographic structures of relevant proteins of the malaria parasite involved in invasion to host cells and 3D NMR structures of High Activity Binding Peptides (HABPs) and their respective analogues, it was found that HABPs are rendered into highly immunogenic and sterile immunity inducers in the Aotus experimental model by modifying those amino acids that establish H-bonds with other HABPs or binding to host's cells. This finding adds striking and novel physicochemical principles, at the atomic level, for a logical and rational vaccine development methodology against infectious disease, among them malaria. © 2010 Elsevier Inc. All rights reserved.